Ethnographic interventions: A strategy and experiments in mapping sociospatial practices - Mounajjed, Nadia; Peng, Chengzhi; Walker, Stephen (Human Technology, 2007)
A growing awareness exists of the possibilities of architectural research adopting working methods used by artists. Many artists have adapted ethnographic methodologies to map site specificity and issues related to community and sociospatial practices. This paper draws on related examples of art practice to formulate a specific research strategy: ethnographic intervention. Ethnographic intervention has three characteristics: (a) ethnographic mapping of spatial practices on site, (b) the possibility of a horizontal replication of the study, and (c) an intervention protocol. We define ethnographic mapping as a critical process directed towards a specific cultural, social, or architectural situation. This involves re-presenting the situation through observing, documenting, videorecording, and photography. We explore the necessity of horizontal replication for producing reliable studies. Finally, we discuss the development of a multi-stage intervention protocol as a creative and flexible instrument, involving design and preparation, data collection, interpretation, and narration. Three case studies illustrate how this strategy has been conceived, applied, and developed at architectural sites. The article concludes with a discussion of the outcomes, usefulness, and possible applications of this strategy in other disciplines.